2018
DOI: 10.1002/hyp.13304
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and its impact on water availability of large international rivers over the mainland Southeast Asia

Abstract: Changes in climate and the resulting hydrologic variability are of great concern in international river basins. Based on observed station data, climate change and its impact on water availability in large international rivers across mainland Southeast Asia (MSA) were investigated by a combined method of trend detection and hydrologic budget balance analysis. This method can be applied easily to other studies to evaluate impacts of climate change on run‐off and water resources at the basin scale. Precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…The potential effect of climate change on the availability of water in the future, especially in the wet season which could potentially have less rainfall, should be considered in the long-term plans on water resource management and agriculture. This is the same as other studies on the impact of climate change on water availability which revealed that the impact of climate change becomes a significant factor influencing changes in precipitation and temperature [9,22,23]. Although the levels of water stress in some watersheds increase due to less rainfall, their environmental water is already safeguarded as the first priority is given to the environmental water in the WSI e2 approach.…”
Section: Resultssupporting
confidence: 76%
“…The potential effect of climate change on the availability of water in the future, especially in the wet season which could potentially have less rainfall, should be considered in the long-term plans on water resource management and agriculture. This is the same as other studies on the impact of climate change on water availability which revealed that the impact of climate change becomes a significant factor influencing changes in precipitation and temperature [9,22,23]. Although the levels of water stress in some watersheds increase due to less rainfall, their environmental water is already safeguarded as the first priority is given to the environmental water in the WSI e2 approach.…”
Section: Resultssupporting
confidence: 76%
“…Furthermore, the seasonal difference of groundwater recharge fluxes/rates may modify groundwater and surface water quality by influencing overland flow, erosion, and solute transport through subglacial soil/rocks (Jasechko et al, ; Vincent et al, ). A great amount of studies on climate change from 1960 to 2010 in the SETP has been carried out with the conclusions that (1) the annual average temperature and all the seasonal temperature increases with the maximum increasing in winter (Fan & He, ; Su et al, ) and (2) the annual precipitation changes little with significant increase in spring (Liu et al, ; Lutz et al, ). In response to the climate change, our study implies that more groundwater recharge during the nonmonsoon seasons could be expectedly induced by increased ice‐melt water and spring precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies for investigating the hydro-meteorological changes over the YLZR basin are available in the literature, few can be found for exploring the trends of the runoff associated with large-scale circulation. Changes in regional air temperature have considerable impacts on the snow cover and glaciers within the YLZR basin [32][33][34], which in turn affects the water resources of the basin [30]. In recent decades, the air temperature within the YLZR basin has shown a significant trend of increase [16].…”
mentioning
confidence: 99%